About the population of the Golden Eagle in the Eastern part of the Kyrgyz Range, Northern Tian Shan, Kyrgyzstan - Anatoly N. Ostashchenko; Andrey Yu. Zakharov (Пернатые хищники и их охрана)
The material for this paper is based on occasional observations of the Golden Eagle (Aquila chrysaetos) over a 30-year period and on breeding data collected from March 21 to April 14, and from May 21 to June 14, 2019, in the foothills and middle mountains of the northern macro slope of the Kyrgyz Range, from the Boom Valley in the east to the Kara-Balta area in the west. This territory is stretching on 170 km. The main goal of the fieldwork was to search for Saker Falcon’s (Falco cherrug) nests, thus information about the Golden Eagle’s nests was collected mostly occasionally. Nevertheless, these data objectively reflect the current state of the population. During the survey period 6 active nests of the Golden Eagle were discovered.